Edukasi penyakit HIV pada masyarakat di Kelurahan Sukamaju, Palembang, Sumatera Selatan - Hudari, Harun; Aprilia Salim, Nelda; Fathurrachman, Alif; Permata, Mega (Fakultas Kedokteran Universitas Sriwijaya, 2024)
. Human Immunodeficiency Virus (HIV) is a disease caused by the HIV virus and transmitted through sexual contact. The spread of HIV in the community continues to occur. Palembang is the highest city in South Sumatra for HIV cases. From January to July 2022, there were 185 HIV cases in Palembang. Many people still do not know about HIV disease and its transmission. There is a lot of confusing news about HIV disease, which can lead to misunderstanding in the community. Good and appropriate education can be a means for people to understand the dangers and transmission. Therefore, it is necessary to increase public knowledge about HIV and its transmission, in order to reduce the incidence of HIV disease and avoid the risk of transmission in the community. Through community service activities by educating the community about HIV, which is done with material presentations and face-to-face meetings and discussions. Measuring the level of knowledge of participants through questionnaires before and after counseling, an increase in understanding of HIV was obtained, with a mean score before 45, and a mean score after 85. This activity increases the understanding score of the prevention and transmission of HIV disease.